PERBANDINGAN MODEL PEMBELAJARAN CORE DAN CARD SORT TERHADAP HASIL BELAJAR SISWA KELAS XI IPS DI SMA NEGERI 3 MUARA BUNGO - Agustina Sitompul, Redi Indra Yudha (Universitas Batanghari Jambi, 2020)
This study aims to determine the comparison of the use of learning models that are applied (CORE learning model and Card Sort) in economic subjects with international trade material in class XI IPS students of SMA Negeri 3 Muara Bungo. Based on the results of the study, an analysis was obtained in the control class (the initial pre-test results were 6 students who passed and in the final pre-test as many as 9 students who passed the KKM). Meanwhile, in the experimental class (the initial pretest results were 8 students who passed and in the final pre-test as many as 15 students who passed the KKM). Meanwhile, in the post-test control class as many as 7 students did not pass and only 12 students passed. And, in the experimental class post-test students who had grades below KKM 21 students and above KKM 4 students. The results obtained an average value of 75. Thus, it can be concluded that the Card Sort learning model can help students actively involved directly in the learning process. Thus, it can be explained that the Card Sort learning model can provide convenience and make students more active in learning. This can be seen from the completeness of student learning. Keyword: CORE, Card Sort, Learning Outcomes.